O impacto da institucionalização da governança de TI no desempenho da governança de TI : uma análise baseada na influência do job crafting - Fantinel , Leonardo Mendes (2019)
The growing interest of organizations on Information Technology Governance (ITG) theme has been justified by the reflection of the changing role and relevance of IT within organizations and, consequently, the need to ensure that it is properly managed. Studies of ITG indicate the existence of two main pillars related to the adoption of ITG. The most common focuses on regulatory and legal aspects and the other, focuses on behavioral aspects, inherent to the individual. In addition, in recent years, the challenging economic situation has increased the pressure on organizations. Instead of waiting for the development of external improvements, organizations are looking internally for methods focused on behavioral aspects to achieve higher levels of performance and productivity. Job Crafting is recognized as a specific form of proactive behavior that encourages employees to improve their own working conditions. This study explored the role of Job Crafting as an impact factor for the IT Governance Institutionalization and, as a consequence, its influence on IT Governance performance. Questionnaires from the literature related to the concepts and, validated in other researches, were used. For this purpose, the hypotheses were validated to verify which Job Crafting variables (Task Crafting, Cognitive Crafting and Relationship Crafting) has an impact on ITG institutionalization and, hypotheses to validate the results in ITG performance. The use of the concept of performance is an important factor as it aims to analyze the final result for organization. In order to analyze the ITG Institutionalization, the ITG objectives of the organization, where the single case study was applied, were used. The research was carried out in a cooperative financial institution with operations in Brazil. A total of 134 employees participated, mostly from IT area or with a strong IT relationship. The Partial Least Squares (PLS) technique was used to confirm the hypotheses. As a result, this study allowed us to identify the degree of relationship between the concepts in a financial organization, opening up opportunities for new research.